The Analysis Study of Effect of Maternal Calcium Supplementation And Pediatric Health : A Comprehensive Systematic Review - Ferianis Setiawati; Anis Prima Dewi, Anis Prima Dewi (International Medical Journal Corp. Ltd, 2025)
Background: Maternal calcium supplementation significantly impacts pediatric health, influencing growth and development. However, the effects on bone growth and mineralization remain inconsistent. Research in low habitual calcium intake populations shows sex-specific outcomes. Pregnancy-induced calcium supplementation has mixed outcomes, with increased mobilization during lactation and minimal impact on offspring growth. Further investigation is needed to improve pediatric health outcomes in diverse dietary calcium intakes. Methods: This systematic review was conducted in strict compliance with the PRISMA 2020 guidelines, ensuring methodological rigor and transparency. The review included only full-text articles published in English between 2013 and 2024, with a focus on high-quality sources. Editorials and review articles lacking a DOI were excluded to maintain the integrity and reliability of the dataset. An extensive literature search was performed using reputable databases, including ScienceDirect, PubMed, and SagePub, to identify studies relevant to the research objectives. Result: The initial database search yielded over 100 publications. Through a rigorous three-stage screening process, eight studies were carefully selected for inclusion based on their relevance and adherence to the established criteria. These selected studies underwent a thorough and critical analysis, offering a detailed evaluation of the impact of maternal calcium supplementation on pediatric health outcomes. Conclusion: Calcium supplementation is crucial for maternal and fetal health during pregnancy, reducing risks like gestational hypertension and pre-eclampsia. World Health Organization recommends 1500-2000 mg daily. Further research is needed to understand sex-specific growth patterns and IGF1-related pathways.